SAT0103 The analysis of reasons of discontinuing biologics in japanese patients with rheumatoid arthritis; from the ninja (national database of rheumatic disease by IR-net in japan). (23rd January 2014) - Yoshimura, M.; Maeda, Y.; Katayama, M.; Watanabe, A.; Tanaka, E.; Tsuji, S.; Harada, Y.; Katada, Y.; Matsushita, M.; Hashimoto, J.; Ohshima, S.; Saeki, Y.
Abstract : Background: Therapy for rheumatoid arthritis (RA) has made rapid progress in recent years. The use of biologics makes it possible to achieve both bio-free remission and drug-free remission. However, biologics are known to increase the risk of infection, and discontinuance rates of biologics are on the rise. Objectives: To evaluate the use of biologics, to compare different biologics, and to investigate the reason why interruption in biologics occurs by Ninja. The Ninja is the largest registry database of Japanese patients with RA. This database consists of data in real world. Methods: We analyzed the use of biologics among 7574 RA patients enrolled in the Ninja during 2010. Characteristics (age, duration of RA, steroid dosage, duration of biologics and rate of remission) of these patients were evaluated. Cases of discontinuation or change in biologics during 2009∼2010, were evaluated. Furthermore, in the cases of discontinuation due to remission we sent out questionnaires to every institution. Results: Among the 7574 RA patients, 1350 (18%) were on biologics, including infliximab (IFX), 306 patients (23%), tocilizumab (TCZ) 220 (16%), etanercept (ETN) 607 (45%), adalimumab (ADA) 171 (13%), abatacept (ABT) 34 (2%), and golimumab (GOL), 10 (1%). There were no significant differences in age, duration of RA, duration of biologic use and steroid dosages. However, MTX dosages were different in each group. The IFX group had the highest number of MTX use (99%), and TCZ group had the least number of patients (35%) (Table 1 ). During the period 2009∼2010, there were 192 cases that discontinued biologics. The reasons for discontinuing biologics were, (1) ineffectiveness (92 cases/48%), (2) adverse events (66/34%), (3) remission (13/6%), (4) others (21/10%) (Fig. 1 ). The results showed that IFX and TCZ might be more effective for inducing bio-free remission than other biologics. No cases of bio-free remission were seen with ETN, suggesting that bio-free remission may be difficult to achieve with ETN. When we analyzed the 13 cases of bio-free remission, we found no difference in patient characteristics compared with all case of biologic use. It was also shown that the bio-free remission can be achieved in patients with long history of RA. Conclusions: ETN was the most commonly used, followed by IFX, and TCZ. IFX and TCZ may achieve bio-free remission more effectively compared with other biologics. In contrast, it may be difficult to achieve bio-free remission with ETN. This might be, however, dependent on the dosage of MTX, as the MTX dosage was less in the ETN group compared to the others. In the TCZ group the cases that maintained the bio-free remission had no MTX use, indicating the potential of TCZ to achieve the bio-free remission without MTX. Disclosure of Interest: None Declared